Pemulihan PTSD dengan Play Therapy pada Anak-anak Korban Bencana Tanah Longsor di Kabupaten Banjarnegara - Mukhadiono, Mukhadiono; Subagyo, Widyo; Wahyudi, Wahyudi (Jurnal Keperawatan Soedirman, 2016)
Children as victims susceptible to Post Traumatic Stress Disorders (PTSD) deserve serious treatment so that the impact is not prolonged and can hinder development. One form of intervention that can be applied namely play therapy. This research aims to determine the PTSD symptom and effect of play therapy on PTSD at the children victims of landslide in Banjarnegara Regency. Research design using quasi experimental pre-posttest with control group. The sample was children victims of landslide aged 4-12 years who experience post-disaster psychological disorders. The sampling method used total sampling. Data analysis used pair t-test. The results showed there were significant differences in scores PTSD before and after the play therapy (0.001) in the intervention group. In the control group, there was no significant difference in score of PTSD before and after the play therapy (0.163). Play therapy was recommended to manage the psychological impact of disaster on children, and their neighborhood may participate in providing toys which are suitable for the local cultures.